BATASAN KETAATAN SANTRI PADA GURU DALAM TAFSIR Q.S. AL-KAHFI AYAT 60-82: RESPONS TERHADAP ISU FEODALISME DI PESANTREN - Isna Zakia Harisa; Santi Lisnawati (Program Pascasarjana IIQ Jakarta, 2026)
Pesantren education emphasizes obedience and khidmah to teachers as essential for attaining knowledge's blessings, yet this concept is often criticized for its potential for feudalism and exploitation. This study aims to formulate normative boundaries for student obedience to align with Islamic morals and prevent unethical power dynamics. Using a qualitative library research method, it focuses on the analysis of Q.S. Al-Kahfi verses 60-82. Data were analyzed through thematic methods (maudhui), referencing authoritative interpretations and classical turāts on teacher-student ethics. The results indicate that obedience in pesantren should be ta’ah masyrū‘ah (prescribed obedience), which is compliance aligned with virtuous values. Obedience becomes prohibited (ta’ah mamnū‘ah) if instructions contradict Divine law or violate human rights, as illustrated by Prophet Musa's critical interruptions of Prophet Khidir's actions. The study concludes that ideal obedience is not blind compliance but an ethical commitment that maintains students' critical thinking and moral integrity. Reconstructing khidmah based on justice is vital to eradicating the impression of feudalism and humanizing students within educational institutions.